Precision measurement of the Ξ−b baryon lifetime - Aaij, Roel; Bachmann, Sebastian; Carus, Leon; Caspary, Rowina; Celani, Sara; Cocha Toapaxi, Carlos; De Cian, Michel; Dittmann, Lucas; Esen, Sevda; Glaser, Fabian; Günther, Paul André; Han, Xiaoxue; et al. (Physical review, 2024)
A sample of 𝑝⁢𝑝 collision data, corresponding to an integrated luminosity of 5.5 fb−1 and collected by the LHCb experiment during LHC Run 2, is used to measure the ratio of the lifetime of the Ξ−𝑏 baryon to that of the Λ0𝑏 baryon, 𝑟𝜏 ≡𝜏Ξ−𝑏/𝜏Λ0𝑏. The value 𝑟𝜏 =1.076 ±0.013 ±0.006 is obtained, where the first uncertainty is statistical and the second systematic. This value is averaged with the corresponding value from Run 1 to obtain 𝑟Run 1,2𝜏 =1.078 ±0.012 ±0.007. Multiplying by the world-average value of the Λ0𝑏 lifetime yields 𝜏Run 1,2Ξ−𝑏=1.578±0.018±0.010±0.011 ps, where the uncertainties are statistical, systematic, and due to the limited knowledge of the Λ0𝑏 lifetime. This measurement improves the precision of the current world average of the Ξ−𝑏 lifetime by about a factor of 2, and is in good agreement with the most recent theoretical predictions.